Faktor-Faktor yang Mempengaruhi Niat Berdonasi Green Waqf di Kalangan Muslim yang Peduli Lingkungan: Peran Mediasi dari Attitude - Faradilah Putri Fauzi; Sulistya Rusgianto; Ririn Tri Ratnasari; Indirwan, Syanisma Khansa (ITB AAS INDONESIA Surakarta, 2025)
This study analyzes the factors influencing the intention to donate to green waqf among environmentally conscious Muslims in Indonesia. The examined factors include green waqf literacy, subjective norms, and access to information media on the intention to donate to green waqf, with attitude acting as a mediating variable. The theoretical foundation of this study is the Theory of Planned Behaviour (TPB). This is a quantitative study that employs the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, with a minimum sample size of 60 respondents. A purposive sampling technique was used, based on three respondent criteria, and the data were analyzed using SmartPLS version 4. This research contributes to the literature by exploring the mediating role of attitude in the relationship between green waqf literacy, subjective norms, and information media access on the intention to donate to green waqf. Additionally, this study specifically focuses on environmentally conscious Muslims, as their knowledge and awareness of environmental issues can play a vital role in supporting and promoting green waqf initiatives. The findings indicate that attitude and subjective norms significantly influence the intention to donate to green waqf among environmentally conscious Muslims in Indonesia. In particular, subjective norms have both direct and indirect effects through attitude, underscoring the importance of social influence in encouraging donation intention. In contrast, green waqf literacy and access to information media show positive but insignificant effects on donation intention, both directly and indirectly through attitude.